Combination of antimicrobials as an approach to reduce their application in aquaculture: Emphasis on the use of thiamphenicol/florfenicol against Aeromonas hydrophila - Assane, Inácio Mateus [UNESP] (2019)
Individual minimum inhibitory and bactericidal concentrations (MIC and MBC) of thiamphenicol (TAP), florfenicol (FFC) and oxytetracycline (OTC) were determined for 49 strains of bacteria isolated from different freshwater fish during disease outbreaks in Brazil. Posteriorly, the in vitro activity and in vivo therapeutic effectiveness of TAP combined with FFC against Aeromonas hydrophila isolated from diseased Nile tilapia, Oreochromis niloticus (Linnaeus, 1758) were evaluated. The in vitro effect of this combination (in terms of the fractional inhibitory concentration index – FICI) was determined by checkerboard microdilution assay, while in vivo analysis was performed via the administration of single doses of TAP (G1: 10 mg/kg), FFC (G2: 10 mg/kg) and selected combinations thereof (G3: 5 mg/kg TAP +2.5 mg/kg FFC, and G4: 2.5 mg/kg TAP +1.25 mg/kg FFC), correspondent to FICI deduction, by gavage to Nile tilapia (70 ± 12 g) challenged by intraperitoneal injection with A. hydrophila. TAP, FFC, and OTC application demonstrated in vitro activity against 55.1%, 71.43% and 55.82% of the evaluated bacteria, respectively. Aeromonas spp. were sensible to the antibiotics both individually and combined (FICI ≤0.75). The two combinations of TAP and FFC (G3 and G4) were as effective in vivo as the recommended individual doses of each antibiotic (G1 and G2), showing greater survival (p <.05) than the unmedicated group (G5). A total of 85.93 ± 5.13% of fish medicated with 62.5% less antibiotics than are currently used to control aeromoniosis survived. These findings demonstrate the potential utility of combination antimicrobials (CA) involving TAP and FFC as an effective approach with which to control aeromoniosis using lower overall doses of antimicrobials with similar efficacy, which may contribute to a reduction in their use without reducing their therapeutic effect during outbreaks in fish farms.